2008
DOI: 10.1038/ejhg.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

A novel splice mutation in PAK3 gene underlying mental retardation with neuropsychiatric features

Abstract: PAK3-related mental retardation represents a rare cause of X-linked mental retardation associated with behavioural symptoms. So far, four families carrying PAK3 mutations have been reported, and in most cases PAK3 dysfunction resulted from missense mutations thought to affect either the catalytic or the N-terminal regulatory domain activity. Here, we report on a Tunisian family of X-linked moderate mental retardation with behavioural symptoms, common dysmorphic features, oro-motor impairment and secondary micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Investigating these molecular mechanisms may have significance in addition to that for psychosis in AD and schizophrenia, considering human genetic research has identified mutations in PAK3 that lead to variants of X-linked intellectual disability associated with psychotic behaviors (Gedeon et al, 2003; Rejeb et al, 2008). Description of the behavioral and associated morphological changes may provide insight into the role of the kalirin-PAK pathway in generating psychosis-associated behaviors in neuropsychiatric disease.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating these molecular mechanisms may have significance in addition to that for psychosis in AD and schizophrenia, considering human genetic research has identified mutations in PAK3 that lead to variants of X-linked intellectual disability associated with psychotic behaviors (Gedeon et al, 2003; Rejeb et al, 2008). Description of the behavioral and associated morphological changes may provide insight into the role of the kalirin-PAK pathway in generating psychosis-associated behaviors in neuropsychiatric disease.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, PAK3 and ARHGEF6 loss-of-function mutations are sufficient to cause a form of X-linked intellectual disability (31, 32, 51), and are thought to work together in a complex (52). Additionally, in one large family pedigree, psychiatric symptoms occur in individuals with a PAK3 coding mutation (A365E) located in the kinase domain that abolishes PAK3 kinase activity (35, 51, 53). PAK1–3 mRNA levels have also recently shown to be differentially expressed in post-mortem studies of schizophrenic brains (54).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the differences, these studies together suggest that mutations of genes involved in the RAC-PAK signaling pathway might cause schizophrenia or other related mental illnesses. Indeed, abnormal expressions or mutations of genes in this RAC-PAK pathway have been reported in human genomic studies of patients with psychotic symptoms (32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%